Osteoblastic Wnt1 regulates periosteal bone formation in adult mice - Wang Fan; Rummukainen Petri; Heino Terhi J.; Kiviranta Riku (Elsevier Inc., 2022)
Compelling clinical data together with genetically modified mouse models have demonstrated that Wnt1 is a key Wnt ligand in bone metabolism, regulating both osteoblast activity and osteoclast differentiation. We have previously shown that deletion of Wnt1 in limb mesenchymal cells leads to severe ostepenic bone phenotype and spontaneous fractures very early after birth. However, the function of Wnt1 in mature skeleton remained unknown. To investigate the role of Wnt1 specifically in adult bone metabolism, we generated an osteoblast lineage-targeted inducible Wnt1 knockout mouse model using tetracycline-controlled Osterix-Cre mouse line (Osx-Cre). In this model, the Cre recombinase expression is suppressed by administering doxycycline (Dox) in drinking water. As expected, Wnt1Osx−/− mice without Dox developed spontaneous fractures early by 3 weeks of age due to severe trabecular and cortical osteopenia. Administration of Dox to Wnt1Osx-Dox−/− and control mice until 4 weeks of age suppressed Wnt1 deletion and completely prevented the fractures. Withdrawal of Dox led to deletion in Wnt1 allele but the fracture incidence progressively decreased in Wnt1Osx-Dox−/− mice at 8 or 12 weeks of age (4 and 8 weeks after Dox withdrawal). Interestingly, deletion of Wnt1 at 4 weeks of age resulted only in a modest and transient trabecular osteopenia that was more pronounced in females and was normalized by 12 weeks of age. However, diaphyseal cortical bone mass and cortical thickness in the femurs were significantly decreased in Wnt1Osx-Dox−/− mice of both genders. Mechanisticly, this was due to impaired periosteal bone formation. Based on our data, in addition to its essential role in early skeletal growth, Wnt1 is an important regulator of modeling-based bone formation and cortical thickness in adult mice.